The impact of legionellosis into fatal outcomes of pneumonia in Irkutsk - A. D. Botvinkin; V. V. Svistunov; E. A. Sidorova; A. E. Makarova; N. A. Kravchenko; L. A. Stepanenko; T. A. Bayanova; M. V. Lemeshevskaya; T. P. Balandina; O. S. Gibteva; E. I. Andaev; S. V. Balakhonov (Фундаментальная и клиническая медицина)
Aim. To study the diagnosis of legionellosis in patients who died because of pneumonia in Irkutsk (2016-2018).Materials and Methods. We performed 65 autopsies of patients who died from pneumonia in Irkutsk (2016-2018), studied their case histories, and interrogated 510 tap water samples for Legionella pneumophila by means of inoculation and polymerase chain reaction.Results. Among 65 fatal pneumonia outcomes registered in Irkutsk during 2016-2018, legionellosis has been confirmed in three cases (4.6%). Two of these patients were at the late stages of HIV infection while the third, 74-yearold, patient had multiple comorbid conditions. Nosocomial infection was suspected in one of these cases. None of these three patients left Irkutsk during the last month of their life. The assumed transmission factor was tap water, as Legionella pneumophila was found in tap water samples collected in 2013 and 2015.Conclusion. Patients with severe pneumonia need screening for legionellosis to perform the correct treatment, particularly during COVID-19 pandemic.